(untitled) (LEARNing Landscapes, 2013)
Using a mixed method research approach of qualitative case study analysis and quantitative surveying, this research1 investigates the development of adolescent digital literacies and their use of mobile devices to further their understandings. More specifically, this article focuses on how a class of adolescents, ages 12-13, reflected on the impact of digital technologies and media on their lives while immersed in a rich media setting, using a social networking site and a combination of their own mobile devices and tablets that were provided to them by their classroom teacher.